The Crucial Changes of Sit-to-Stand Phases in Subacute Stroke Survivors Identified by Movement Decomposition Analysis - Mao, Yu Rong; Wu, Xiu Qin; Zhao, Jiang Li; Lo, Wai Leung Ambrose; Chen, Ling; Ding, Ming Hui; Xu, Zhi Qin; Bian, Rui Hao; Huang, Dong Feng; Li, Le (Frontiers in Neurology, 2018)
Abstract Objective: The aim of this study was to detect the key changes during sit-to-stand (STS) movement cycle in hemiparetic stroke survivors using a five-phases kinematic and kinetic analysis. Methods: Twenty-five subacute stroke survivors and seventeen age-matched healthy adults participated in this study. The kinematic and kinetic parameters during STS cycle were measured using three-dimensional motion analysis system with force plates. The five standard phases of STS cycle were identified by six timing transitional points. Results: Longer total time as well as larger changes were observed at the initial phase (phase I, 0.76±0.62s VS 0.43±0.09s; p=0.049) and at the end of hip and knee extension phase (phase IV, 0.93±0.41s VS 0.63±0.14s; p=0.008) in the stroke group than healthy group. Time to maximal knee joint moment was significantly delayed in the stroke group than in the control group (1.14±1.06s VS 0.60±0.09s, p<0.001). The maximal hip flexion was lower during the rising phase from seated position on the affected side in the stroke group than in the control group (84.22±11.64°VS 94.11±9.40°; p=0.022). Ground reaction force was lower (4.61±0.73N VS 5.85±0.53N, p<0.001) in the affected side of the stroke group than in the control group. In addition, knee joint flexion was significantly lower at just-standing phase (T4) and at end point (T5) (5.12±5.25° VS 8.21±7.28°, p=0.039; 0.03±5.41° VS 3.07±6.71°, p=0.042) on the affected side than the unaffected side. Crucial decrease of knee joint moment at abrupt transitory (T2) and the maximal moment was also observed on the affected side in comparison with the unaffected side (0.39±0.29 Nm/kg VS 0.77±0.25 Nm/kg, p<0.001; 0.42±0.38 Nm/kg VS 0.82±0.24 Nm/kg, p<0.001). Conclusions: The findings of movement decomposition analysis provided useful information to clinical evaluation of STS performance, and may potentially contribute to the design of rehabilitation intervention program for optimum functional recovery of STS after stroke.